Climate and changing winter distribution of alcids in the Northwest Atlantic - Veit, Richard R.; Manne, Lisa L. (Frontiers in Ecology and Evolution, 2015)
Population level impacts upon seabirds from changing climate are increasingly evident, and include effects on phenology, migration, dispersal, annual survivorship and reproduction. Most population data on seabirds derive from nesting colonies; documented climate impacts on winter ecology are scarce. We studied interannual variability in winter abundance of six species of alcids (Charadriiformes, Alcidae) from a 58-year time series of data collected in Massachusetts 1954-2011. We used counts of birds taken during fall and winter from coastal vantage points. Counts were made by amateur birders, but coverage was consistent in timing and location. We found significant association between winter abundance of all six species of alcids and climate, indexed by North Atlantic Oscillation (NAO), at two temporal scales: 1.) Significant linear trends at the 58-year scale of the time series; and 2.) Shorter term fluctuations corresponding to the 5-8 year periodicity of NAO. Thus, variation in winter abundance of all six species of alcids was significantly related to the combined short-term and longer-term components of variation in NAO. Two low-Arctic species (Atlantic Puffin and Black Guillemot) peaked during NAO positive years, while two high Arctic species (Dovekie and Thick-billed Murre) peaked during NAO negative years. For Common Murres and Razorbills, southward shifts in winter distribution have been accompanied by southward expansion of breeding range, and increase within the core of the range. The proximate mechanism governing these changes is unclear, but, as for most other species of seabirds whose distributions have changed with climate, seems likely to be through their prey.